Negative Transfer of Indonesian into English: A Study in SMPN 01 Sungai Pinyuh in Academic Year 2021/2022 - Silfiana; Sudarsono; Dwi Riyanti (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
First language plays an important role when it comes to learning second language. The process of first language interference in learning second language is called transfer. There are two classifications of transfer. The Positive transfer and negative transfer. This research was done to analyze the negative transfer of Indonesian into English of beginner students who learn English as foreign language. The method of the research was in qualitative descriptive study with the participants of grade-7 students in SMPN 01 Sungai Pinyuh in Academic Year 2021/2022. The data were collected by interviewing the participants and collecting worksheets from the participants. The researcher analyzed the data by using content analysis and transcription. The finding of the study showed that there were many errors made by the students that related to negative transfer and students tended not to realize that they were making mistakes. The results of this research were expected to be useful information for other teachers as a reference in teaching foreign languages and for other researchers with the same topic.